Efektivitas Kinerja Aparatur Inspektorat Daerah Kabupaten Pohuwato Provinsi Gorontalo - Anggriani Makasisahe; Juriko Abdussamad; Fenti Prihatini Tui (Gorontalo State University, 2022)
ABSTRACT Based on the results of research analyzed in the field that (1) the performance of the quality of the Pohuwato Regency Regional Inspectorate Apparatus in carrying out its functions as the obligations of the Pohuwato Regency Regional Inspectorate Apparatus, in this study the researchers decided to use only three aspects in measuring the effectiveness of the performance of the Pohuwato Regency Regional Inspectorate Apparatus, namely, Quality , Quantity and Timeliness. Based on the results of the research Quality of performance, using four dimensions to see the results of the effectiveness of the performance of the Regional Inspectorate Apparatus of Pohuwato Regency, namely, Tangible (Intangible), Reliability (Reliability), Responsiviness (Responsiveness), Assurance (Guarantee). The regions have satisfied the Quantity of Performance, seen from the results of research in carrying out their duties and functions realized through setting targets according to rational capabilities and mechanisms based on SOPs. Punctuality, looking at the results of research from the timeliness of the Inspectorate Apparatus in providing public services, it has been realized through punctuality in entering and leaving work, leaving the workplace according to permits, and maximizing working time. (2) The supporting and inhibiting factors for realizing the effectiveness of the performance of the Apparatus at the Regional Inspectorate of Pohuwato Regency are, Supporting factors of work motivation, the apparatus has supported the effectiveness of the performance of a satisfactory form of income, the creation of a good working relationship between the apparatus. Human resources, this has hampered the effectiveness of performance because there is still a lack of Government Internal Supervisory Apparatus (APIP), especially functional officials, which are not comparable to the object of inspection (audit) and locations scattered in the Pohuwato Regency area. In addition, the lack of availability of facilities in the form of computers hinders the effectiveness of the performance of the Pohuwato Regency Regional Inspectorate apparatus.